Transformasi Pembelajaran PPKn Sekolah Dasar di Era Digital Melalui Pemanfaatan Platform Civic Edu - Mohassin Mohassin; Nazar Eka saputra; Dwi Elsa Romadhoni; Mujtahidin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The advancement of digital technology in education demands learning innovations that integrate technology with character building for students. This study aims to examine the transformation of Pancasila and Citizenship Education (PPKn) learning in elementary schools through the use of the CivicEdu platform. This study used a descriptive qualitative approach at SDN Socah 04, involving teachers and fifth-grade students as research subjects. Data were collected through semi-structured interviews and questionnaires, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results show that the use of CivicEdu can improve the quality of PPKn learning, making it more interactive, structured, and student-centered. In addition, this platform facilitates teachers in classroom management, monitoring the learning process, and implementing evaluations more effectively, and receives a positive response from students, marked by increased interest and participation in learning. CivicEdu also has the advantage of integrating character education, national values, and strengthening the Pancasila Student Profile into the learning process. Thus, CivicEdu can be an alternative relevant digital learning platform to support the implementation of the Independent Curriculum and strengthen student character in elementary schools.